Assessment of innovation and foreign direct investment: An investigation of OECD countries. (20th September 2020) - Li, Boying; Chang, Chun‐Ping; Zheng, Mingbo
Abstract: Using a panel cointegration method incorporating structural breaks and cross‐sectional dependence, this paper explores the long‐run equilibrium relationship between innovation and foreign direct investment (FDI) in 30 OECD countries. The results from the panel stationary test show that FDI and innovation variables follow a stationary process with several structural breaks over the period 1999–2018. The results also suggest an equilibrium relationship with structural breaks between FDI and innovation in OECD countries. The panel dynamic OLS model with breaks further reveals that FDI is positively associated with innovation performance and vice versa in OECD countries. Therefore, this paper sheds light on the relationship between FDI and innovation in OECD countries.